Ultra-low profile solar-cell-integrated antenna with a high form factor - Ali, Ahmed; Wang, Heesu; Lee, Jaejin; Ahn, Yeong Hwan; Park, Ikmo (Scientific Reports, 2021)
This paper presents an ultra-low-profile copper indium gallium selenide (CIGS) based solar cell integrated antenna with a high form factor. A tiny slot was etched from the solar cell to develop an ultra-low-profile solar-cell-integrated antenna. This tiny slot increases the form factor due to the small clearance area from the solar cell. A ground-radiation antenna design method was applied in which lumped elements were employed inside the tiny slot for antenna operation. Another substrate was used under the solar cell for designing the feeding structure with lumped elements connected to the tiny slot using via holes. A prototype was fabricated and measured to verify the operation of a built-in solar-cell antenna and validate the simulated results. The measured results demonstrate that the solar-cell-integrated antenna covers the entire frequency range of the Industrial Scientific Medical band, from 2.4 to 2.5 GHz, with a maximum gain of 2.79 dBi and radiation efficiency higher than 80% within the impedance bandwidth range. Moreover, the proposed design has an ultra-low-profile structure of only 0.0046 λo, where λo represents the free space wavelength at 2.45 GHz, and a high form factor of 99.1% with no optical blockage. The antenna and solar cell were designed to avoid affecting the performance of each other using the radio-frequency decoupler.